Antimicrobial agents : antibacterials and antifungals - Bryskier, Andre (ASM Press, 2005)
Annotation Antimicrobial Agents: Antibacterials and Antifungals is a significant revision of an original French reference published by Ellipses in 1999. Offers hundreds of antibiotics and antimicrobial compounds: in development, experimental, and in use. Provides a thorough update of the original French edition published in 1999, plus critical new material. Presents comprehensive coverage of chemistry and synthesis, classification, structure-activity relationships, mechanisms of action and resistance, breakpoints, in vitro/in vivo activities, epidemiology, pharmacokinetics, metabolism, and adverse eventsFeatures over 1,200 illustrations, over 1,500 tables, and more than 3,000 references. Presents new, extensive chapters covering helicobacter pylori and methicillin-resistant Staphylococcus aureus (MSRA).